Managing the challenges of schooling in Ibadan rural settings of Oyo state, Nigeria (2009)
There are many challenges facing schooling in a typical Nigerian rural setting, hence this tudy was undertaken to verify how these challenges could be managed in some rural settings which are quite close to an urban centre. This is a non-experimental study. Simple random sampling was used to select 45 teachers and 150 students from 5 secondary schools in Egbeda and Lagelu local government area of Ibadan less city of Oyo state, Nigeria. Two structured questionnaires were administered respectively on the two categories of subjects. The data so gathered were analysed using percentages and chi-square. findings included: trekking long distance to get to school, teachers' unwillingness to live among the people in these communities due to lack of social amenities and the concomitant unbearable living conditions in thses settings. The roads are also "un-motorable" with its consequent hardship in accessing these areas. The school buildings are equally in a state of dilapidation. It was discovered that if schooling in thses settings were to be effectively managed, then, stakeholders would have to invest in the provision of social amenities such as"motorable" roads, provision of rural electricity, mini-markets, as well as hospitals. It was thus suggested that both government and other stakeholders should provide the necessary social amenities to attract teachers to rural areas, as well as provide extra perquisites to attract teachersto these communities.